A agressividade nas interações virtuais: análise das estratégias de im/polidez em comentários a uma publicidade veiculada no youtube - Carla Eliane Quaresma (2018)
With the technological innovations connected to the Internet, new types of social relations emerge. Important and rapid changes in the forms of interaction and communication become part of lives of an increasing number of people, they can be in private or professional activities. In this context, new media are in expansion, in popularization, making possible to their users the exchange about many themes and, consequently, a great exposition and defense of personal points of view. Digital platforms like YouTube that, besides the sharing of videos, also allow activities of verbal exchange, become spaces of complex interpersonal relations at a distance. In this way, the main objective of this research is to investigate the face work, specifically, the aggressive use of the speech acts in the attack and defense of faces performed by interacting subjects in this environment. Considering the immense universe of interactions in the digital platform, it was necessary a space-time clipping. Our option concentrated on commentaries, conversations and discussions registered in the YouTube among users that reacted to specific and polemical advertising campaign for perfumes to the Valentines day in Brazil, conveyed in 2015, named Entregue-se às sete tentações de Egeo de O Boticário (Immerse yourself in seven temptations from Ego of O Boticário), in which included homoaffective couples. Taking into consideration this polemic, we analysed conversations characterized by polite and impolite speech acts and in strategies of conservation of the faces among the interacting users. This dissertation is based on the Facess theory proposed by Goffman (2011[1967]), in the postulated of Brown and Levinson (1987) about politeness and in the contributions of Culpeper (2011, 1966) about impoliteness in the speech acts. The theoretical framework offers the necessary basis to support the analytical procedures about the selected corpus. By the discourse-linguistic analysis, interlocutor subjects, whose reactions injure the principle of politeness and good manners in the social interactions, mostly when they address the other participants involved in the process of communication.